2002
DOI: 10.1109/ted.2002.805576
|View full text |Cite
|
Sign up to set email alerts
|

Large area, ultra-high voltage 4H-SiC p-i-n rectifiers

Abstract: This paper reports the design, fabrication and high temperature characteristics of 1 mm 2 , 4 mm 2 and 9 mm 2 4H-SiC p-in rectifiers with 6 kV, 5 kV, and 10 kV blocking voltage, respectively. These results were obtained from two lots in an effort to increase the total power levels on such rectifiers. An innovative design utilizing a highly doped p-type epitaxial Anode layer and junction termination extension (JTE) were used in order to realize good on-state as well as stable blocking characteristics. For the 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(38 citation statements)
references
References 10 publications
1
37
0
Order By: Relevance
“…As a typical example, the forward characteristics of SiC pin diodes having an i-layer thickness of 200 µm (28 kV class) are presented in Figure 3, where the carrier lifetime in the i-layer was changed from 1 µs to 100 µs (an analytical expression for the characteristics of a pin diode and brief discussion are given in Note S1). As expected, the characteristics are remarkably improved by increasing the carrier lifetime, which is consistent with the studies on lower-voltage SiC pin diodes reported in literature [33,34]. Note that the carrier lifetimes longer than 10 µs do not contribute very much to reduction of the forward voltage drop.…”
Section: Of 15supporting
confidence: 91%
“…As a typical example, the forward characteristics of SiC pin diodes having an i-layer thickness of 200 µm (28 kV class) are presented in Figure 3, where the carrier lifetime in the i-layer was changed from 1 µs to 100 µs (an analytical expression for the characteristics of a pin diode and brief discussion are given in Note S1). As expected, the characteristics are remarkably improved by increasing the carrier lifetime, which is consistent with the studies on lower-voltage SiC pin diodes reported in literature [33,34]. Note that the carrier lifetimes longer than 10 µs do not contribute very much to reduction of the forward voltage drop.…”
Section: Of 15supporting
confidence: 91%
“…As a wide bandgap semiconductor material, silicon carbide(SiC) is an ideal materials for high frequency, high power and anti-radiation devices which can operate in high temperature and hostile environments [I , 2,3]. SiC is also an attractive wide bandgap material for ultraviolet(UV) detection owing to its wide bandgaps, material maturity and stability [4,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…PiN diodes fabricated in SiC offer high current density operation with on-state voltage drop values comparable to stacked Si devices, reduced switching losses due to thinner epitaxial layers and high temperature operation [2], [4]. Si PiN diodes suffer from slow switching speeds beyond 3 kV due to thicker base regions and subsequent higher levels of stored charge.…”
Section: Introductionmentioning
confidence: 99%